Muhadarah sebagai Strategi Pengembangan Public Speaking Skill Santri di Pondok Pesantren Roudlotut Tholibin Probolinggo - Taufiqurrohman, Achmad; Khoiriyah, Khoiriyah (MASALIQ, 2025)
This study aims to examine the effectiveness of muhadarah activities in enhancing public speaking skills among students at Pondok Pesantren Roudlotut Tholibin Kademangan Probolinggo. Muhadarah, as a public speaking exercise focused on delivering sermons or speeches, is an essential part of the educational curriculum in pesantren. Public speaking skills are deemed crucial for students as preparation to become competent leaders and communicators in society. This research adopts a qualitative approach with a case study method in a pesantren setting. Data was collected through observation, interviews, and document analysis. The findings indicate that consistent practice of muhadarah helps students improve their confidence, effective communication skills, and ability to organize and deliver messages clearly. Muhadarah activities play a vital role in shaping students' speaking abilities while reinforcing religious and social values beneficial for daily life. The study recommends strengthening the muhadarah program as part of a sustainable educational strategy in pesantren.